THE ISSUE OF PEOPLES' HISTORY AND ETHNIC ROOTS IN THE WORK "FIRDAVSU-L-IQBAL" (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the issues of the history and ethnic origins of peoples as presented in Firdavsu-l-iqbol. The study analyzes genealogies, historical narratives, and the author’s views on the origins of various peoples from a scholarly perspective. In addition, the article explores information related to the formation of Central Asian peoples, their historical roots, and mutual interactions as reflected in the work, and evaluates the significance of Firdavsu-l-iqbol as an important source in historical studies.